Урожай ядовитых ягодок: Роман / Д. А. Донцова - Донцова Дарья (Иронический детектив, 2002)
Экземпляры: ф.14 (2004) / Инвентарный номер: 48286 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 67 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44